In vitro kinetics of reticulocyte subtypes : maturation after red blood cell storage in additive solution-1 (AS-1) (2018)
Background: Reticulocytes are immature red blood cells containing RNA remnants. Their population kinetics has been documented under various in vivo and in vitro conditions, including after storage of red blood cells in blood banks. The purpose of this study was to describe the influence of blood bank storage on the kinetics of reticulocyte disappearance by in vitro culturing. Method: Samples of reticulocyte-enriched fractions (Percoll density-gradient) were obtained over different storage times from six red blood cell units stored in additive solution-1 (AS-1). Reticulocyte fractions were then cultured in enriched media at 37 °C and analyzed by flow cytometry with thiazole orange taking into account hemolysis. Results: Density-gradient enriched reticulocyte fractions were obtain from standard red blood cell units with <1% of reticulocytes. An exponential drop of reticulocytes was observed in cultures. The time taken for reticulocyte disappearance in cultures was shorter with increased blood bank storage time (144 ± 46 h at 0.5 weeks of storage and 15 ± 14 h in the sixth week). High fluorescence reticulocytes disappeared completely in 42.5 ± 8.5 h, medium fluorescence reticulocytes in 73.4 ± 20.8 h and low fluorescence reticulocytes in 269.9 ± 98.8 h in red blood cell units stored for half a week. These times significantly decreased in red blood cell units stored for more time. Conclusion: In vitro reticulocyte disappearance was significantly faster after prolonged storage of red blood cell units at 4 °C. The in vitro half-life at 0.5 weeks of storage was not significantly different from the values reported for fresh venous blood, but after the sixth week of storage, the half-lives were shorter. The possible explanation is that blood bank storage does not cause irreversible damage to the human reticulocyte maturational machinery. © 2018 Associação Brasileira de Hematologia, Hemoterapia e Terapia Celular